Review of the placement of Flatoides monilis (Hemiptera: Flatidae: Flatoidinae) - Levia, Nathaniel N.; Bartlett, Charles R. (Zootaxa, 2026)
The genus Flatoides Guérin-Méneville is an Afrotropical taxon in the subfamily Flatoidinae, currently containing several misplaced Neotropical species. The placement of the Jamaican species Flatoides monilis Van Duzee, 1907, is reviewed, and a new genus, Chloroflatoides gen. nov., is described for this species. A key to the American genera of Flatoidini and an amended description are also provided for Chloroflatoides monilis gen. & comb. nov.